Assessing the impact of respirable dust and heavy metals on mechanics’ health in automobile workshops - Nor Ashikin, Sopian; Nik Muhammad Danish Haikal, Nik Hasrul Hisham; Muhamad Aiman, Saharin Sah; Zarifah, Shahri; Noor Haziqah, Kamaludin (AIP Publishing, 2025)
Prolonged exposure to air pollutants and heavy metals may increase the risk of developing cancer and multiple acute respiratory illnesses in any polluted workplace. This study aimed to evaluate heavy metal exposure and its impact on mechanics’ health in the selected automobile workshops. A validated questionnaire on socio-demographic information, working experience, work practice, and workshop environment has been distributed to mechanics at six workshops in Kuantan and Gambang, Pahang. The respirable dust was collected for a full working period of 6 hours using active sampling. Meanwhile, the assessment of heavy metals exposure has been performed following the National Institute of Occupational Safety and Health (NIOSH) Manual of Analytical Method 7302. The prediction of the incremental lifetime cancer risk of heavy metals exposure was based on the inhalation route of exposure and according to the USEPA approach. The range of respirable dust for the workshops in Kuantan is between 2.77 to 4.86 mg/m3. Meanwhile, the concentration of respirable dust for workshops in Gambang ranges from 1.47 to 4.93 mg/m3. The mechanics in Gambang are exposed to a higher concentration of Fe and Ag as compared to the mechanics in Kuantan. The cumulative cancer risk for all mechanics for Cr exceeded the safe limit. This finding highlighted the necessity for workshop management to take a proactive approach to reducing respirable dust and heavy metals exposures, especially through the improvement of safe work practices and providing adequate ventilation at the workplace.